Amniotic Membrane Scaffolds Support Organized Muscle Regeneration in A Murine Volumetric Muscle Defect Model. Issue 9 (14th September 2022) - Awad, Mohamed; Kurlander, David E.; Kotha, Vikas S.; Malone, Kevin; Davidson, Edward H.; Kumar, Anand R.
Abstract : Background: Current treatment for volumetric muscle loss is limited to muscle transfer or acellular collagen scaffold (ACS) therapies that are associated with donor site morbidity and nonfunctional fibrosis, respectively. The aim of this study is to assess the utility of amniotic membrane scaffold (AMS) for volumetric muscle loss treatment. Methods: Murine quadriceps defects were created and randomized to three groups (n = 5/group): untreated controls, ACS, and AMS. In vivo muscle regeneration volume was quantified by MRI and microcomputed tomography. Muscle explants were analyzed using standard histology and whole-mount immunofluorescence at 8 weeks. Results: The cross-sectional muscle regeneration ratio was 0.64 ± 0.3 for AMS, 0.48 ± 0.07 for ACS, and 0.4 0 ± 0.03 for controls as assessed by MRI ( P = 0.09) and 0.61 ± 0.28 for AMS, 0.50 ± 0.06 for ACS, and 0.43 ± 0.04 for controls as assessed by microcomputed tomography ( P = 0.2). Histologically, AMS demonstrated significantly higher cellular density (900 ± 2 70 nuclei/high powered field) than ACS (210 ± 36) and control (130 ± 4) groups ( P = 0.05). Immunofluorescence for laminin (AMS 623 ± 11 versus ACS 339 ± 3 versus control 115 ± 7; P < 0.01) and myosin heavy chain (AMS 509 ± 7 versus ACS 288 ± 5 versus control 84 ± 5; P = 0.03) indicated greater organized muscle fiber formation with AMS. Conclusion: AMS mediated muscle healing was characterized by increased cellular infiltration and organized muscle formation when compared with controls and ACS.